Vaccine Refusal Among Pregnant Women: A National Survey of Obstetrician-Gynecologists. (4th October 2017) - O'Leary, Sean; Riley, Laura; Lindley, Megan C; Allison, Mandy; Crane, Lori; Hurley, Laura; Beaty, Brenda; Brtnikova, Michaela; Albert, Alison; Fisher, Alison; Jiles, Angela; Kempe, Allison
Abstract: Background: Little is known about vaccine refusal among pregnant women. Our objectives were to describe, among a nationally representative sample of obstetrician-gynecologists (ob-gyns): 1) perception of frequency of and reasons for vaccine refusal among pregnant women; and 2) strategies used to address vaccine refusal and perceived effectiveness of those strategies. Methods: E-mail and mail survey among ob-gyns conducted 3–6/2016. Results: The response rate was 69% (331/477). Pregnant women more commonly refused influenza (flu) vaccine compared with tetanus-diphtheria-acellular pertussis (Tdap) vaccine (Table 1). Conclusion: Ob-gyns perceive refusal of flu vaccine is more common among their pregnant patients than refusal of Tdap. Emphasizing the risk of disease to the fetus may be an effective strategy to increase uptake. It will be important to validate these findings in a patient sample. Disclosures: All authors: No reported disclosures.